(untitled) (Carte Romanze, 2023)
The language of the mediaeval Waldensian manuscripts is an Occitan variety that can be traced back to the Alpine region as a whole, although it remains an isolated case in the context of the documentation found so far. Over the course of time, the characteristics of the scripta have been compared by various scholars with the contemporary oral varieties of the present-day Waldensian Valleys, the area where the manuscripts were found, reaching some very different conclusions. In the present contribution, after having framed some of the problematic aspects of the comparison between the medieval literary variety and the present-day dialects, we propose to reconsider decisive aspects in the light of the analysis conducted, by way of example, starting from the paradigm of possessive adjectives.